2020
DOI: 10.1155/2020/3451215
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Postconditioning Upregulates Phosphorylated Connexin 43 in the Middle Cerebral Artery Occlusion Model and Is Probably Associated with the TGF-β1/Smad2/3 Signaling Pathway

Abstract: Aim. Connexin 43 (Cx43) has been identified to be important for cerebral ischemia/reperfusion (I/R) injury as well as protection from it. This study was aimed at investigating the relationship between phosphorylated Cx43 (p-Cx43), transforming growth factor-β1 (TGF-β1)/Smad2/3 signaling pathway, and isoflurane postconditioning (ISPOC), which has effects on brain injury in rats with cerebral ischemia/reperfusion (I/R) injury. Methods. The middle cerebral artery occlusion (MCAO) model was induced in 96 male Spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Increasing evidence has demonstrated that anesthetic drugs, such as isoflurane and propofol, play vital roles in regulating molecular pathology changes in the central nervous system and neurocognitive behaviors. It is necessary to design a group of mice solely undergoing isoflurane anesthesia as a control to exclude drug interference in cognitive deficits postoperation [38,39,57]. Therefore, more experiments are still needed to confirm the effect of Smad7 in regulating the cognitive decline induced by anesthesia surgery in the future, which would provide an important theoretical basis for the molecular pathological mechanism and clinical intervention of cognitive impairment caused by anesthesia surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has demonstrated that anesthetic drugs, such as isoflurane and propofol, play vital roles in regulating molecular pathology changes in the central nervous system and neurocognitive behaviors. It is necessary to design a group of mice solely undergoing isoflurane anesthesia as a control to exclude drug interference in cognitive deficits postoperation [38,39,57]. Therefore, more experiments are still needed to confirm the effect of Smad7 in regulating the cognitive decline induced by anesthesia surgery in the future, which would provide an important theoretical basis for the molecular pathological mechanism and clinical intervention of cognitive impairment caused by anesthesia surgery.…”
Section: Discussionmentioning
confidence: 99%
“…All the mice were administered 50 μL of 0.2% ropivacaine subcutaneously for postoperative analgesia and then kept on a heating pad to recover spontaneously. All surgical procedures were completed within 10 min to reduce the impact of isoflurane, which has been confirmed to affect neurocognition by regulating signaling pathways [38,39]. Considering that anesthesia and surgery cannot be completely separated, the mice in the control group underwent neither anesthesia nor surgery.…”
Section: Anesthesia and Surgerymentioning
confidence: 99%
“…PDCD4 expression is not only regulated by miR-21-5p, but also at the level of transcription, translation and protein degradation [25], therefore mechanisms influenced by isoflurane with opposing effects than miR-21-5p could be responsible for maintaining the PCDC4 expression. For example, isoflurane is able to increase transforming growth factor beta-1 (TGF-β1) levels [26], which in turn induces apoptosis via PDCD4 overexpression [25].…”
Section: Discussionmentioning
confidence: 99%
“…Post-injury conditioning was investigated with a range of stimuli. Iso urane post-conditioning (for 60 minutes immediately post-MCAO) was shown to reduce neurological severity score (NSS), infarct volume and neuronal survival or density in a TGF-β1-dependent manner [103][104][105] . Remote ischemic postconditioning generated an increase in TGF-β1 expression and phosphorylation of Smad2/3 which correlated with reduced infarct volume and improved NSS, con rmed by TGF-β1 knockdown 106 .…”
Section: Tgf-β1 In Pre-clinical Ischemic Stroke Studiesmentioning
confidence: 99%